Pengembangan Sistem Informasi Pengelolaan Donatur Anak Panti Asuhan Berbasis Web Menggunakan Metode SDLC - Zulfahmi Syahputra (LKP KARYA PRIMA KURSUS, 2025)
The development of a web-based donor management information system for an orphanage aims to simplify donor data recording, donation transaction management, and reporting with higher speed and accuracy. The system replaces manual processes that often lead to data entry errors and delays in information processing. The method applied is the System Development Life Cycle (SDLC), consisting of requirement analysis, system design, implementation, testing, and maintenance. The system provides features for managing donor data, foster child records, donation transactions, and online publication of orphanage activities. Implementation results indicate improved efficiency, reduced data errors, and enhanced transparency, which contributes to greater donor trust in fund management.